Electronic Structure and Band Alignment of LaMnO3/SrTiO3 Polar/Nonpolar Heterojunctions. Issue 1 (19th November 2018) - Kaspar, Tiffany C.; Sushko, Peter V.; Spurgeon, Steven R.; Bowden, Mark E.; Keavney, David J.; Comes, Ryan B.; Saremi, Sahar; Martin, Lane; Chambers, Scott A.
Abstract: The behavior of polar LaMnO3 (LMO) thin films deposited epitaxially on nonpolar SrTiO3 (001) (STO) is dictated by both the LMO/STO band alignment and the chemistry of the Mn cation. Using in situ X‐ray photoelectron spectroscopy, the valence band offset (VBO) of LMO/STO heterojunctions is directly measured as a function of thickness, and found that the VBO is 2.5 eV for thicker (≥3 u.c.) films. No evidence of a built‐in electric field in LMO films of any thickness is found. Measurements of the Mn valence by Mn L ‐edge X‐ray absorption spectroscopy and by spatially resolved electron energy loss spectra in scanning transmission electron microscopy images reveal that Mn 2+ is present at the LMO surface, but not at the LMO/STO interface. These results are corroborated by density functional theory simulations that confirm a VBO of ≈2.5 eV for both ideal and intermixed interfaces. A model is proposed for the behavior of polar/nonpolar LMO/STO heterojunctions in which the polar catastrophe is alleviated by the formation of oxygen vacancies at the LMO surface. Abstract : The mechanism that alleviates the polar catastrophe of LaMnO3 /SrTiO3 heterojunctions is revealed using in situ and ex situ spectroscopies. The valence band offset is much larger than previously theorized, which impacts carrier confinement. Mn 2+ is observed on the LaMnO3 surface, indicating that oxygen vacancies have formed. These oxygen vacancies compensate the built‐in electric field arising from the polar catastrophe.